Sulfur Dioxide and Emergency Department Visits for Stroke and Seizure - Mieczysław Szyszkowicz; Eugeniusz Porada; Neil Tremblay; Eric Grafstein (Stroke Research and Treatment)
The purpose of this study was to assess an association between ambient sulfur dioxide and the number of emergency department (ED) visits for ischemic stroke and seizure. The study used data collected in a Vancouver (Canada) hospital in the years 1999–2003. Daily ED visits diagnosed as ministroke, stroke, or seizure were investigated using the case-crossover technique. Conditional logistic regression models were applied to estimate the odds ratios (ORs) and their respective 95% confidence intervals (CIs). The models included temperature and relative humidity in the form of natural splines. The results were reported for an increase in interquartile range ((IQR), IQR=1.9 ppb for SO2). Positive and statistically significant associations were obtained for SO2 and ischemic stroke for all patients (OR=1.12; CI 1.02, 1.23; lag 3) and for female patients (OR=1.17; CI 1.01, 1.33; lag 0). In the case of ED visits for seizure, for female patients the results were also statistically significant (OR=1.15; CI 1.02, 1.28; lag 1 and OR=1.18; CI 1.05, 1.32; lag 2). These findings suggest that cases of ischemic cerebrovascular accidents are associated with acute exposure to ambient sulfur dioxide.